Chrysanthemum field - Rosenberg, Richard (Philadelphia Evening Bulletin, 1979)
"Pots of yellow Chrysanthemums, used to decorate the altar where Pope John Paul II celebrated Mass during his visit to Philadelphia, are stored in Fairmount Park for the winter. The flowers are kept in an area near Ford Road and the Strawberry Mansion Bridge." With clipping